(untitled) (Eurasian Research Bulletin, 2023)
In the context of work on the draft of a new edition of the Civil Code of the Republic of Uzbekistan, the relevance and scientific novelty of legal regulation and the grounds for establishing the fact of an unknown absence are determined. The role and significance of the institute of unknown absence are argued in the consideration of some specific situations. The unknown absence of a person is considered as a certain legal phenomenon, which can give rise to certain problems of a legal nature. Various grounds for signs of the legal state of the unknown absence of a person are analyzed. Considered are not only the grounds for recognizing a person as missing, but also the circumstances that are subject to proof in this category of civil cases. The conclusion is formulated about the loss by the missing person of subjective personal and property rights to the extent that other persons participating in the legal relationship show interest. Proposals have been formulated regarding the legal consequences for a person recognized as missing, to improve civil, family and civil procedural legislation.